Barriers and facilitators to preventive cancer screening in Limited English Proficient (LEP) patients: Physicians' perspectives. (14th October 2015) - Bruce, Kelly; Schwei, Rebecca; Park, Linda; Jacobs, Elizabeth
Abstract : Background: Limited English Proficient (LEP) patients receive fewer recommended preventive screenings than English-speaking patients. Studies have explored patients' perceptions of the factors that contribute to this disparity, but little research has focused on physicians' perceptions. The objective of this paper is to describe physicians' perceptions of the barriers and facilitators to preventive cancer screening in LEP patients, based on semi-structured interviews with eight primary care physicians from Wisconsin, systematically coded to illuminate important themes. It was found that a variety of barriers specifically hinder LEP patients' receipt of cancer screening, including poor language proficiency, lack of transportation, unfamiliarity with the concept of prevention, complex scheduling systems, poor interpretation, and limited physician time to discuss preventive care. While physicians identified many factors that facilitate preventive screening in general, they mentioned few that are perceived as specific to LEP patients. We found that primary care physicians attribute the low rates of preventive cancer screening among LEP populations to a variety of patient, provider, interpreter, and system factors, most of which go beyond simple language barriers. Interventions designed to reduce these barriers and enhance the impact of identified facilitators should be multifactorial and designed to engage primary care physicians.